Strategies of Vibrio parahaemolyticus to acquire nutritional iron during host colonization - León-Sicairos, Nidia; Angulo-Zamudio, Uriel A.; de la Garza, Mireya; Velazquez-Roman, Jorge A.; Flores-Villaseñor, Hector M.; Canizalez-Roman, Adrian (Frontiers in Microbiology, 2015)
Iron is an essential element for the growth and development of virtually all living organisms. As iron acquisition is critical for the pathogenesis, a host defense strategy during infection is to sequester iron to restrict the growth of invading pathogens. To counteract this strategy, bacteria such as Vibrio parahaemolyticus have adapted to such an environment by developing mechanisms to obtain iron from human hosts. This review focuses on the multiple strategies employed by V. parahaemolyticus to obtain nutritional iron from host sources. In these strategies are included the use of siderophores and xenosiderophores, proteases and iron-protein receptor. The host sources used by V. parahaemolyticus are the iron-containing proteins transferrin, hemoglobin and hemin. The implications of iron acquisition systems in the virulence of V. parahaemolyticus are also discussed.